2013
DOI: 10.1080/13504630.2013.835509
|View full text |Cite
|
Sign up to set email alerts
|

Not a simple coffee shop: local, global and glocal dimensions of the consumption of Starbucks in China

Abstract: This article examines the ways in which Chinese consumers engage with foreign brands, looking specifically at their perceptions and experiences of Starbucks. Rather than assuming an inherent conflict between global and local meanings, or collectivist and individualist values, we examine the accomplished meaning of foreign brands: how Chinese consumers make sense of Starbucks, and what their engagements with the brand can tell us about the interplay between the local, global and glocal in the consumption of Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
(43 reference statements)
0
31
1
Order By: Relevance
“…Other authors also highlighted these factors [ 51 , 84 , 85 ]. Numerous studies confirm that the main motive for drinking coffee, and thus the main factor for the purchase of coffee by consumers, is its flavor and aroma, and the feeling of pleasure when consuming it [ 50 , 52 , 57 , 68 , 77 , 86 , 87 , 88 , 89 , 90 ], as well as the atmosphere in which coffee is consumed and the emotions that accompany the consumer while drinking it [ 77 ]. Other factors include social recognition of the value of coffee and its stimulating “magic effect”, as well as its physical impact on the body, e.g., the ability to aid digestion or increase blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also highlighted these factors [ 51 , 84 , 85 ]. Numerous studies confirm that the main motive for drinking coffee, and thus the main factor for the purchase of coffee by consumers, is its flavor and aroma, and the feeling of pleasure when consuming it [ 50 , 52 , 57 , 68 , 77 , 86 , 87 , 88 , 89 , 90 ], as well as the atmosphere in which coffee is consumed and the emotions that accompany the consumer while drinking it [ 77 ]. Other factors include social recognition of the value of coffee and its stimulating “magic effect”, as well as its physical impact on the body, e.g., the ability to aid digestion or increase blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies found that the use of texts, brands, and metaphorical images on coffee packaging moderately influenced product expectations, intrinsic quality perception, and purchase intention [89]. Brand identification is especially important in the coffeehouse market [87,88,89,90]. Drinking a specific coffee brand (e.g., Starbucks) represents a status symbol and way of life for consumers [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Third, coffee shops provide good quality customer service and experience (Aries and Eirene 2015), which turns people into repeat customers and enhances consumer loyalty (Yu and Fang 2009). Fourth, coffeehouses offer comfortable space for socialisation and business meetings (Maguire and Hu 2013), which is facilitated by active uptake of technology, such as free Wi-Fi (Wu 2017). Lastly, brand recognition and social status play an important role in the success of branded coffee shops, especially in the Asia Pacific, where consumers perceive visits to coffeehouses as a means of societal selfexpression and brand loyalty (Kang et al 2011).…”
Section: Coffee Shopsmentioning
confidence: 99%